1995
DOI: 10.1017/s0021859600073329
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nitrogen on the development of Septoria epidemics in winter wheat

Abstract: S U M M A R YField experiments were undertaken at the University of Wales, Aberystwyth over two seasons to investigate the effects of N fertilizer rate and timing on the development of Septoria diseases (principally Septoria tritici) in winter wheat and its subsequent effect on crop growth. Rates of 100,200 and 300 kg/ha N were applied at GS23, GS30, or split (GS23/30/38) in 1985/86 and 100 and 250 kg/ha N at GS23, GS30, GS23/30, or GS23/30/37 in 1987/88. Foliar diseases were allowed to develop or were control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
1
6

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 17 publications
6
53
1
6
Order By: Relevance
“…In common with other studies comparing Napplication rates in winter wheat (Prew et al, 1983;Leitch & Jenkins, 1995), we found least disease on the crops receiving least N. Previous reports have suggested that this is because low-N crops become senescent more rapidly, so that green leaf area (GLA) becomes limiting on disease progress. However, our study suggested that S. tritici was responsible for most of the senescence recorded in both high-and low-N treatments.…”
Section: Effect Of Crop Husbandry On Disease Progresssupporting
confidence: 89%
“…In common with other studies comparing Napplication rates in winter wheat (Prew et al, 1983;Leitch & Jenkins, 1995), we found least disease on the crops receiving least N. Previous reports have suggested that this is because low-N crops become senescent more rapidly, so that green leaf area (GLA) becomes limiting on disease progress. However, our study suggested that S. tritici was responsible for most of the senescence recorded in both high-and low-N treatments.…”
Section: Effect Of Crop Husbandry On Disease Progresssupporting
confidence: 89%
“…In 2001, fungicide application again failed to produce yield increase at low N rate (Table 4) because of small overall disease severity in both sprayed (4.6 %) and untreated plots (2.5 %). Lower incidence of foliar diseases under less intensive N fertilization has been reported by several authors (Guy and Oplinger 1989, Leitch and Jenkins 1995, Olesen et al. 2003).…”
Section: Resultssupporting
confidence: 58%
“…Mechanisms suggested in the literature from studies on a range of pathosystems include changes in biochemical processes in the plant, such as a decrease in the content of phenol with an increase of N application (Király, 1964), changes in crop canopy structure (Tompkins et al ., 1992), or a favourable microclimate as a result of increased crop density and canopy size (Darwinkel, 1980; Oerke & Schönbeck, 1990; Bryson et al ., 1995; Danial & Parlevliet, 1995; Leitch & Jenkins, 1995; Jensen & Munk, 1997). For powdery mildew development on wheat, leaf N content was found to be more important than canopy size (Olesen et al ., 2003b).…”
Section: Introductionmentioning
confidence: 99%